2012
DOI: 10.5539/cco.v1n1p32
|View full text |Cite
|
Sign up to set email alerts
|

Integrin-Mediated Actions of Thyroid Hormone Analogues on Tumor Cell Chemosensitivity, Integrin-Growth Factor Receptor Crosstalk and Inflammatory Gene Expression

Abstract: Tetraiodothyroacetic acid (tetrac) and its nanoparticulate formulation induce apoptosis in cancer cells, oppose angiogenesis about xenografted human tumors and block cancer cell repair of double-stranded DNA breaks. These nongenomic actions of tetrac are initiated at a tetrac-thyroid hormone receptor on plasma membrane integrin v3. In this review, we examine additional anti-cancer activities of tetrac formulations at v3 and what is known about their mechanisms. These activities include 1) reversal of cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 55 publications
1
8
0
Order By: Relevance
“…Furthermore, there is growing evidence that thyroid hormones increase the motility of avb3-expressing immune cells, and, possibly by similar mechanisms, nerve cell migration (De Vito et al 2012). An array of growth factors, including PDGF, insulin-like growth factor 1 (IGF1), HGF, EGF and VEGF, as well as chemokines, such as RANTES/CCL5, CCL22 and, to a lower extent, SDF-1/CXCL12 and their respective receptors, have been implicated in MSC migration (Ponte et al 2007, Spaeth et al 2008) and many of these have been shown in this and other studies to be regulated by thyroid hormones via differential gene expression and receptor crosstalk (Davis et al 2011, Hercbergs et al 2012. Modulation of recruitment and engraftment efficiency of MSCs is of clinical interest, in settings of tissue regeneration, in the context of general tumour growth and the emerging field of MSC-based gene delivery in cancer therapy (Knoop et al 2011, Knoop et al 2013, Uchibori et al 2014.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, there is growing evidence that thyroid hormones increase the motility of avb3-expressing immune cells, and, possibly by similar mechanisms, nerve cell migration (De Vito et al 2012). An array of growth factors, including PDGF, insulin-like growth factor 1 (IGF1), HGF, EGF and VEGF, as well as chemokines, such as RANTES/CCL5, CCL22 and, to a lower extent, SDF-1/CXCL12 and their respective receptors, have been implicated in MSC migration (Ponte et al 2007, Spaeth et al 2008) and many of these have been shown in this and other studies to be regulated by thyroid hormones via differential gene expression and receptor crosstalk (Davis et al 2011, Hercbergs et al 2012. Modulation of recruitment and engraftment efficiency of MSCs is of clinical interest, in settings of tissue regeneration, in the context of general tumour growth and the emerging field of MSC-based gene delivery in cancer therapy (Knoop et al 2011, Knoop et al 2013, Uchibori et al 2014.…”
Section: Discussionmentioning
confidence: 99%
“…While tetrac is known to exert low-grade thyromimetic effects intracellularly (Moreno et al 2008), it was shown to have anti-tumour effects in vitro and in vivo in various cancer models via modulation of tumour cell proliferation, apoptosis and angiogenesis by T 3 /T 4 antagonistic action mediated through integrin avb3 (Yalcin et al 2009, Davis et al 2011. Further anti-tumour activity of tetrac includes the suppression of invasiveness/metastasis, increased radio-and chemosensitisation and antagonism of inflammation (Davis et al 2011, Hercbergs et al 2012, Yalcin et al 2013. These effects are thought to be largely mediated by avb3 expressed on the tumour cells themselves.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These actions are regulated via the αvβ3 integrin and are MAPK-mediated. Disruption of the thyroid-integrin signaling by use of RGD or tetrac, a specific blocker of the thyroid hormone binding site upon the integrin [16, 17], impaired the production of MMP-9 in myeloma cell lines and primary BM cells from myeloma patients.…”
Section: Introductionmentioning
confidence: 99%